Simulation of solar cells operation using computer programming - 299089 Royston Anak Jikin; Samsudi Sakrani, supervisor; Fakulti Sains (2006)
Project Paper (Sarjana Muda Sains (Fizik Industri)) - Universiti Teknologi Malaysia, 2006